Early versus Delayed Mobilization Post-Operative Protocols for Primary Lateral Ankle Ligament Repair: A Systematic Review and Meta-analysis. Issue 4 (16th October 2019) - Vopat, Matthew L.; Tarakemeh, Armin; Morris, Brandon; Hassan, Maaz; Garvin, Pat; Zackula, Rosalee; Mullen, Scott; Schroeppel, Paul; Vopat, Bryan G.
Category: Ankle, Sports, Post-op protocol Introduction/Purpose: Lateral ankle instability represents a common orthopaedic diagnosis. Nonoperative treatment through focused physical therapy provides satisfactory results in most patients. Some patients, however, experience persistent chronic lateral ankle instability despite appropriate nonoperative treatment. These patients may require stabilization which can include primary lateral ligament repair to restore ankle stability. Optimal post-operative rehabilitation of lateral ankle ligament repairs remains unknown, as surgeon vary in how they balance protection of surgical repair with immobilization with the need for ankle joint mobilization to restore range of motion. The aim of this review is to provide insight into early and delayed mobilization post- operative protocols in patients undergoing primary lateral ankle ligament repairs to determine if an optimal evidence-based post- operative rehabilitation protocol exists in the literature. Methods: Following PRIMSA criteria, a meta-analysis using the PubMed/Ovid Medline database was performed (10/11/1947- 10/16/2017). Manuscripts that were duplicates, non-lateral ligament repair, biomechanical and non-English language were excluded. Protocols were reviewed and divided into two categories; early mobilization (within 3 weeks of surgery) and delayed mobilization (after 4 weeks of surgery). Return to sport, outcome scores (AOFAS, Karlsson scores) and complications of both populations were recorded and statistically analyzed. Results: 31 out of 1, 844 studies met the criteria for the final analysis, representing 1, 608 patients undergoing primary lateral ligament repair. There was no statistical difference in pre-operative AOFAS scores with delayed mobilization having a score of 67.3 and early mobilization having a score of 67.6 (p<0.639). There was statistical significance in the post-operative AOFAS score comparing delayed mobilization group versus early mobilization group with 91.8 versus 98.8, respectively (p<0.001) and post- operative Karlsson scores with values of 90.0 vs. 92.2 in delayed versus early respectively (p<0.001). Return to sport in the delayed group was 11.8 weeks versus 10.9 in early (p<0.044). No significant difference was found in complication rates between groups with delayed having a rate of 3.7% and early 4.8% (p<0.389). Conclusion: Patients may benefit from early mobilization protocols after lateral ankle ligament repair. The early mobilization protocols group had improved functional outcomes and decreased time until return to sport without a difference in complications. More studies are needed to definitively evaluate early versus delayed rehabilitation protocols due to heterogeneity of the studies.